Answer: (f-g)(x) is equivalent to f(x) - g(x)
So that would be (2x²-5) - (x²-4x-8) = 2x² - x² + 4x + 8 - 5 = x² + 4x + 3
Hope this helps.
Answer:
1.49 x
hours
Step-by-step explanation:
1 day=24hours
1 year=365 days
365days=24 x 365=8760hours
17 years
= 8760hours x 17
=148920hours
=1.4892 x
= 1.49 x
hours
Answer:
No
Step-by-step explanation:
To determine if (- 5, - 5) is a solution
Substitute x = - 5 into the inequality and compare answer to y
- 2(- 5) + 4 = 10 + 4 = 14 > - 5 ← the y- coordinate
Thus (- 5, - 5) is not a solution to the inequality
Answer:
y=0.25x-6
Step-by-step explanation: